STRATEGI EFEKTIF DALAM PENGAJARAN DI SEKOLAH DASAR MELALUI PEMETAAN KARAKTERISTIK PESERTA DIDIK - Huda, Ikmal Choirul; Renny Kumalasari, Mega (Program Studi PGSD, FKIP, Universitas Mataram, 2024)
This study explores effective teaching strategies in elementary schools through student characteristic mapping. Understanding the unique nature of each student is essential to designing inclusive and effective learning experiences. This study examines key aspects of student characteristics, including physical, intellectual, emotional, social, moral, spiritual, talents/interests, and family/cultural background. By mapping these areas, teachers can better tailor their instruction to meet the diverse needs of students. This study highlights differentiated instruction as an effective approach to applying insights from student characteristic mapping. This strategy, called differentiated instruction, allows teachers to tailor content, processes, and products based on students’ learning styles, readiness, and interests. This paper discusses the urgency of student characteristic mapping in elementary education, where basic skills and attitudes are developed. It outlines specific steps for implementing differentiated instruction, including in-depth student identification, lesson planning, method selection, and ongoing evaluation. Case studies from Indonesian elementary schools demonstrate the positive impact of this approach on student engagement and improved learning outcomes. Overall, student characteristic mapping provides a foundation for creating more responsive, inclusive, and student centered learning environments in elementary education.